Electron impact catalytic dissociation: Two-Bond Breaking by a Low-Energy Catalytic Electron - Davis, Daly; Vysotskiy, Victor P.; Sajeev, Yesodharan; Cederbaum, Lorenz S. (Angewandte Chemie. International edition, 2011)
Upon impact of a low-energy electron on a neutral molecule, an intermediate metastable electron-molecule compound is formed. This species can undergo electron-catalyzed two-bond breaking or cycloelimination, as in the simplest case of the cyclobutane-ethylene conversion (see scheme). This mechanism is illustrated for the quadricyclanone-norbornadienone cycloelimination reaction using ab initio methods, and its generality appears promising.